Avaliação da aprendizagem: contribuições para a formação humana integral de discentes do ensino médio integrado - Leitão, Raimar Antônio Rodrigues (2020)
Evaluation is a subject that is inserted in the most knowledge diverse areas and in formal and non-formal spaces, whether in the ambit of school education or in other spheres and social organizations. Nevertheless, in the school space, a series of discussions and expectations regarding its actions, purposes and developments are been generated in the course of the history of education. In this sense, this research had the general aim of analyzing the learning evaluation contribution related to promote the Integral Human Formation of finalist students from the Integrated Technical Course in Agriculture, campus Eirunepé (2017-2019). This study was part of the Educational Practices in Professional and Technological Education (EPT) research line, specifically linked to the Macroproject 3 - Educational Practices in the Integrated Curriculum, according to ProfEPT/2018 Regulation. This was a qualitative research based on the dialectical method of case study strategy – and used bibliographic and documentary research, conversation circles, participant observation and interviews –, which intended to analyze the processes and aspects that involved the theme and the participants (students and teachers) through the collected data. After the collection, the data were submitted to content analysis within the Bardin (2016) proposal. Among the main theoretical references in the Professional and Technological Education field, as well as in the Integral Human Formation field, we used Ciavatta (2005), Frigotto (2012), Moura (2007; 2015) and Ramos (2008) ideas. Considering the learning evaluation, the theoretical support was Esteban (2003), Freire (1996), Hoffmann (2003; 2014), Libânio (2006), Luckesi (2000; 2011), Perrenoud (1999), Vasconcellos (2014) and Zabala (1998), among other scholars. In this context, we highlight the evaluation formative perspective as a theoretical parameter in the field of evaluation to support observations and data analysis. Based on the information found in this research, as an Educational Product, it was elaborated an Evaluation Course in Booklet format (printed and digital), which has as target audience the Integrated High School teachers, in order to provide a contribution to the improvement of quality evaluation processes. From the obtained data, we noted that the basic conditions for a learning evaluation which favors the Integral Human Formation on Integrated High School, should prioritize all the students considering their multiple learning capacities and externalization of what they learn. As we believe, just relying on understanding of the students in their completeness, it will be possible to evaluate them with equity, seeing the teaching and learning actions resizing in order to it can move towards its human development and plenary formation.